Spearman’s Rank Correlation and Factorial Analysis: Socio-Demographic Characteristics of Diabetic Hypertensive Patients Presenting to a Tertiary Care Hospital - Kapoor, Monika (Indian Journal of Pharmacy Practice)
Objectives: The main objective of this paper is to explore exploratory factor analysis and Spearman’s Rank Correlation which indicates the relationship between the duration of the disease with socio-demographic characteristics of the patients presenting to the hospital. Study Design: Prospective Observational Study. Methods: The study was carried out in the Department of Medicine of the Punjab Institute of Medical Science and Hospital (PIMS), Jalandhar for a period of 6 months from June 2018 - November 2018 after Recieving approval from the Institutional Ethics Committee. After calculating the sample size using Epi Info, the study was conducted on a total of 250 patients. The study was analyzed using SPSS version 24. Results: The age group of the study was 22 to 86 years. According to the Kolmogorov Smirnov (KS) and Shapiro-Wilk (SW) p value was found to be p=0.009a and p=0.058b respectively. Age was found to be normally distributed because the p-value was found above the cut-off point with Skewness -0.200, Kurtosis 0.178 and standard error 0.762. It was observed that there is a significant moderate positive correlation between age and duration of HTN (r = 0.408, p = 0.001). Further analysis was observed that age, social habits and physical activity also has a wide impact on the duration of disease. Conclusion: Numerous factors are observed to be directly associated with the socio-demographic characteristics of the patients. During the study, it was observed that age, social habits and physical activity also has a wide impact on the duration of the disease itself.
Keywords: Exploratory factor analysis; Spearman’s Rho; Duration of Diabetes and HTN; Comorbidities; Social habits; Physical activity; Age.